Pharyngalgia: self-treatment or the qualified help of the family doctor? - Podpletnia O.A.; Potapova T.M. (Medičnì Perspektivi)
Self-treatment by pharmaceuticals is an actual problem of health care, patients more and more often address to the pharmacist, not visiting the family doctor for various reasons. In this case, the role of the pharmacist is not limited to the release of non-prescription drugs "at the request or insistence of the patient." This situation requires from the pharmacist not only specialist knowledge of the pharmacology of drugs, but also a professional approach to the diagnosis and treatment of symptoms and syndromes. Pharmacoepidemiologic research of the department of General and Clinical Pharmacy showed that about 93% of population of Dnepropetrovsk use pharmaceuticals without preliminary consultation with the doctor. The pharmacist in time having recognized the leading symptoms, having provided symptomatic treatment with OTC-medicines and having convinced the patient to ask for the qualified help of the doctor is a link between the patient and the family doctor. In the article by the example of one of the most common symptoms – pharyngalgia – difficulties of diagnostics which is impossible without a deep knowledge of clinical medicine are shown and the need of administering prescription drugs in most cases is confirmed, which in turn is possible only after consultation of the family doctor in most cases.